2018
DOI: 10.1021/acs.jafc.8b03169
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Characteristics of Steamed Notoginseng by an Efficient LC–MS/MS Method for Simultaneously Quantifying Twenty-three Triterpenoids

Abstract: Steamed Panax notoginseng (SNG) has been widely used as a restorative medicine instead of the raw one, but its pharmacokinetic profile is entirely unknown. To address this, we've developed an LC-MS/MS method with high efficiency and sensitivity for simultaneous quantification of 23 triterpenoids (notoginsenosides Fa, Fc, R, 20( S)-R, 20( R)-R, ginsenosides F, Rb, Rg, Rd, Re, Rb, 20( S)-Rh, 20( R)-Rh, Rh, R k, R k, 20( S)-Rg, 20( S)-Rg, 20( R)-Rg, Rg, C-K, 20( S)-PPT, 20( S)-PPD) from SNG in rat plasma. This va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…The T max values of the three saponins from Powder 5 were much smaller than those of the other powders, and the C max of ginsenoside Rg 1 was higher than that of other powders, indicating that after the administration of Powder 5, the saponins are absorbed quickly in the body and reach a peak rapidly. After Powders 4 and 5 were administered by intragastric administration, notoginsenoside R 1 and ginsenosides Rg 1 and Rb 1 exhibited double peaks in the C-T gures (Powder 4 was more obvious), which were consistent with results previously reported [21,33]. This result could be due to differential rates of absorption along the gastrointestinal tract, and this prolonged residence time of the drug in the body could be bene cial to the maintenance of the drug effect, but the mechanisms of the double peaks remain to be determined [34,35].…”
Section: In Vivo Studysupporting
confidence: 91%
“…The T max values of the three saponins from Powder 5 were much smaller than those of the other powders, and the C max of ginsenoside Rg 1 was higher than that of other powders, indicating that after the administration of Powder 5, the saponins are absorbed quickly in the body and reach a peak rapidly. After Powders 4 and 5 were administered by intragastric administration, notoginsenoside R 1 and ginsenosides Rg 1 and Rb 1 exhibited double peaks in the C-T gures (Powder 4 was more obvious), which were consistent with results previously reported [21,33]. This result could be due to differential rates of absorption along the gastrointestinal tract, and this prolonged residence time of the drug in the body could be bene cial to the maintenance of the drug effect, but the mechanisms of the double peaks remain to be determined [34,35].…”
Section: In Vivo Studysupporting
confidence: 91%
“…Here we demonstrated the interactions between 5 sort of ginsenosides from red ginseng and HSA by ITC and molecular docking. These results indicates that these ginsenosides were transported through the bloodstream to various parts of the body by binding with HSA after absorption by intestine, and also the interaction with HSA may result in the strong stabilities of these ginsenosides in vivo demonstrated in previous study (Zhu et al, 2018). Because of the cavities and depressions on the surface of HSA molecule, it can transport many substances by interacting with them.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, when ginsenosides are ingested through diet, due to their poor bioavailability and easy degradation in the digestive tract, we cannot guarantee whether ginsenosides will be eventually transported to the places where they are needed. Previous studies have shown that some ginsenosides are absorbed by small intestinal villi through passive diffusion (Paek et al, 2010), and ginsenosides used in this study have a considerable bioavailability and stability in vivo (Zhu et al, 2018). Here we demonstrated the interactions between 5 sort of ginsenosides from red ginseng and HSA by ITC and molecular docking.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, PPT often provides higher recovery of analytes when compared with solid‐phase extraction (SPE) and liquid–liquid extraction (LLE) after optimizing the most appropriate precipitation reagent (Rathod et al, ; Wang et al, ). For example, Zhu et al () compared the ratios of methanol to acetonitrile from 1:1 to 5:1 (v/v), and ultimately chose 4:1 (v/v) as the optimal ratio for plasma sample extraction to achieve maximal recovery and minimal matrix effects. Occasionally, the significant matrix effect cannot be eliminated when PPT was applied, resulting in the low sensitivity of analyte detection (Guo et al, ).…”
Section: Sample Clean‐up and Recoverymentioning
confidence: 99%